A DEA Approach to Performance-Based Budgeting of Formula One Constructors. (April 2014) - Gutiérrez, Ester; Lozano, Sebastián
This article assesses the relative efficiency of teams participating in Formula One (F1) World Constructors' Championship. A nonparametric method based on data envelopment analysis (DEA) has been used. The aim is to measure each constructor's performance, comparing its efficiency relative to all other competing constructors. The study uses financial and performance data to assess the proximity of the constructors to the best practices frontier. The analysis has been made considering the results of the 2003, 2006, 2008, 2010, and 2011 F1 seasons. In order to create a parsimonious DEA model, a variable screening method for dimensionality reduction is considered. The results indicate that, generally, a substantial reduction should be made to the constructors' budget over the seasons in order to be efficient as compared to the identified benchmarks. In addition, scale efficiency reveals that most constructors operate below their most productive scale size.